Perlindungan Hak Cipta Terhadap Warisan Budaya Bangsa Indonesia Ditinjau Dari Undang – Undang Hak Cipta No. 28 Tahun 2014 - Nur Salsabila Koswara; Rani Apriani (Peneliti.net, 2022)
The purpose of this research is to protect copyright and the government's role in the cultural heritage of the Indonesian nation in terms of Copyright Law no. 28 of 2014. With a normative juridical legal research method, it is concluded: 1. Copyright protection of the cultural heritage of the Indonesian nation in terms of Copyright Law no. 28 of 2014 is stipulated in CHAPTER V Article 38, Article 39 and Article 60- The protection of the copyright law on the cultural heritage of the Indonesian nation covers two main areas, the first is the protection of the cultural heritage of the Indonesian nation where the identity of the creator is unknown. The second area is the protection of the cultural heritage of the Indonesian nation where the creator is known. 2. The role of the Indonesian government in protecting the copyrights of Indonesian cultural heritage by taking actions to take inventory, safeguard and maintain by creating a data base of the nation's cultural heritage, where as a protective measure, the government currently has a National Data Center for Communal Intellectual Property managed by the Directorate General Intellectual Property (DJKI) of the Ministry of Law and Human Rights to make an inventory of data on Communal Intellectual Property owned by the Indonesian nation.